The Effect of Inflation, BI Rate, and Exchange Rate on Murabahah Financing with Gold Price Moderation - Muammar; Hanif; Nur Wahyu Ningsih (Department of Islamic Banking, 2026)
Purpose – This study uses the price of gold as a moderating variable to investigate how inflation, the BI Rate, and the rupiah exchange rate affect murabahah funding at Islamic commercial banks between 2015-2024. Methodology – The impact of independent variables on the dependent variable is investigated in this study using quantitative methods and multiple linear regression. The moderating variable is tested using moderation regression analysis. Findings – According to the study, murabahah finance is positively affected by inflation and the rupiah exchange rate, but not by the BI Rate. Based on the moderation regression test results, gold prices can mitigate the effects of inflation on murabahah finance, but they cannot mitigate the effects of the rupiah exchange rate or the BI Rate. Implications – Islamic banks should pay more attention to changes in inflation and exchange rates when managing murabahah financing. They should continue emphasizing the benefits of the fixed margin system, which does not depend on interest rates. Future research is expected to incorporate additional variables that reflect internal banking dynamics and broader macroeconomic conditions. Originality – The originality of this research is, first, the research period on murabahah financing over the past 10 years, which will certainly yield different findings due to the different time frame used. Second, the price of gold has not been examined as a moderating factor for murabahah financing in Islamic commercial banks.